Hubungan Citra Pelayanan dengan Pemanfaatan Layanan Rawat Inap di Rumah Sakit Jember Klinik Tahun 2018 - Agustin Dwi Rahayu; Christyana Sandra; Sri Utami (Pustaka Kesehatan, 2021)
The role of the hospital’s image greatly influences the success of activities in acting as a hospital. There are five dimensions to measure the image of service through the company image (corporate image): corporate identity, physical environment, contact personnel, service offering, and corporate individuality. The study is a quantitative study aimed at analyzing the image of service and utilization of inpatient services at Jember Klinik Hospital. Results showed that of the 90 respondents, respondents had good ratings of corporate identity (60%), physical environment (68.9%), contact personnel (97.8%), service offering (74.4%), corporate individuality (70%), and service utilization (77.8%). Data analysis showed that the variables which have a significant correlation with the utilization of inpatient services at Jember Klinik Hospital are corporate identity (0.007), physical environment (0.010), service offering (0.009), corporate individuality (0.043), and contact personnel (0.065) has no correlation with the utilization of inpatient services at Jember Klinik Hospital. The study concluded that the assessment of service images at Jember Klinik Hospital is good, but the physical environment variable has a low rating regarding inadequate parking facilities. The strategic location and type of service provided by the hospital are essential factors in the utilization of health services.